DECODING RADIAL CLUB HAND - DR. ABDUL HADISHAREEF (International Journal of Pharma and Bio Sciences, 2014)
6 month old case of radial club hand reported to us with upper limb deformity, absent thumb and difficulty to extend elbow since birth. Early genetic and systemic evaluation is very much essential because associated syndromes should be treated early, like fanconi’sanaemia. Fanconi anemia needs early diagnosis which is crucial for the child and family, because it needs bone marrow transplant which is the only cure. Early diagnosis will buy time to search for suitable donor.